If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 = f + -3f + 6f Combine like terms: f + -3f = -2f 32 = -2f + 6f Combine like terms: -2f + 6f = 4f 32 = 4f Solving 32 = 4f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-4f' to each side of the equation. 32 + -4f = 4f + -4f Combine like terms: 4f + -4f = 0 32 + -4f = 0 Add '-32' to each side of the equation. 32 + -32 + -4f = 0 + -32 Combine like terms: 32 + -32 = 0 0 + -4f = 0 + -32 -4f = 0 + -32 Combine like terms: 0 + -32 = -32 -4f = -32 Divide each side by '-4'. f = 8 Simplifying f = 8
| -9z+5z=-7+9z+2 | | 6(x+1.39)=5x | | 8x-26=6x-4 | | 4+3v-7v-2+v= | | w^2-10w+16= | | -3r+10=2r | | 7x-99=2x+1 | | -2(c+3)=76 | | 2w=5(6) | | -4.6x+1.1=21.9 | | w-5w+w+10w+w+w= | | 2-3x=40-8x-1x-10 | | 8m-10=-1+9m | | 2x=1x+15 | | 9.2x=25.76 | | 3+5+4= | | 6x-4y+y+-3x+x= | | 10-5d=7d-10 | | 12x^2-311-9th=0 | | S^2+5s+5=0 | | x+10(2x)=x+25(x) | | -6y=25 | | 3n-6-6-2n=4n-3 | | -6y=19 | | 0.75m+14=1.78m-10.3936 | | -9-2=4x+1-3x | | 2(2x+5)-3=25 | | 4x+4+x-1= | | 12*12+45+12= | | 14f+6f=4(5)square | | -8=-(-x+4) | | 5t-3=12+7t |